Activity in Neurons of a Putative Protocerebral Circuit Representing Information about a 10 Component Plant Odor Blend in Heliothis virescens - Løfaldli, Bjarte B.; Kvello, Pål; Kirkerud, Nicholas; Mustaparta, Hanna (Frontiers in Systems Neuroscience, 2012)
The olfactory pathway in the insect brain is anatomically well described from the antennal lobe to the mushroom bodies and the lateral protocerebrum in several species. Less is known about the further connections of the olfactory network in protocerebrum and how information about relevant plant odorants and mixtures are represented in this network, resulting in output information mediated by descending neurons. In the present study we have recorded intracellularly followed by dye injections from neurons in the lateral- and superior protocerebrum of the moth, Heliothis virescens. As relevant stimuli, we have used selected primary plant odorants and mixtures of them. The results provide the morphology and physiological responses of neurons involved in a putative circuit connecting the mushroom body lobes, the superior and the lateral protocerebrum, as well as input to superior and lateral protocerebrum by one multiglomerular antennal lobe neuron and output from the lateral protocerebrum by one descending neuron. All neurons responded to one particular mixture of ten primary plant odorants, some of them also to single odorants of the mixture. Altogether, the physiological data indicate integration in protocerebral neurons of information from several of the receptor neuron types functionally described in this species.